Kto mi rozwiąże najszybciej zadanie dostanie premie:
a) 2x + (2x - y) - (x + 2y) + (-2x - y) =
dla x = -3 i dla y = - 1/2
b) 2x - (-5x + 2y - z) + (-x + y + z )
dla x = 1/3 y = -1 i z = 0,1
c) (2a + 3b) + (-3a + b + 2) - -4a - b - 3)
dla a = 4 i b = -4

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-02T22:02:48+01:00
A) 2x + (2x - y) - (x + 2y) + (-2x - y) =2x+2x-y-x-2y-2x-y= x-4y
-3-4*1/2 = -3-2 = -5
b) 2x - (-5x + 2y - z) + (-x + y + z )= 2x+5x-2y+z-x+y+z= 6x-y+2z
6*1/3-(-1)+2*0,1 = 2+1+0,2 = 3,2
c) (2a + 3b) + (-3a + b + 2) - (-4a - b - 3)= 2a+3b-3a+b+2+4a+b+3 = 3a+5b+5
3*4+5*(-4)+5 = 12-20+5 = -8+5 = -3
1 1 1